PENERAPAN AKUNTANSI LINGKUNGAN DARI SUDUT INDUSTRI PERHOTELAN - Rizki, Novia; Priyambodo, Victoria Kumanintyas; Sukma, Paradisa; Prasidya, Tusta C.I.T (Balance : Jurnal Akuntansi dan Bisnis, 2023)
This study aims to determine, identify and analyze efforts to implement green accounting or environmental accounting by Hotel X. The analysis used in this study differs from that used in previous studies in that it divides all forms of environmental accounting efforts into environmental accounting indicators which The 3-star hotel that serves as the research object also differs from earlier studies. The method used in this research is descriptive qualitative with a case study. Data was collected through interviews and observation. The research object is Hotel X, a 3-star hotel located in Gili Trawangan, Lombok, Indonesia. The result shows that of the four environmental accounting indicators, Hotel X is the most dominant in terms of internal failure costs. This is because the company has not maximized environmental prevention costs and environmental detection costs. External failure costs that are currently being incurred by Hotel X, are only related to cleaning and turtle conservation costs